DESIGNING AN INSET COURSE FOR THE COLLEGE SUBJECT TEACHERS TO TEACH IN ENGLISH FOR INTERNATIONAL PROGRAMS - Dr. Suharno (PAROLE: Journal of Linguistics and Education, 2013)
In  globalization  era  making  a  broader  networking  among universities  is  urgent. To  realize such  a cooperation  several Indonesian universities are opening international programs but the common  problem faced  in  higher  education  level  is  the  lack  of human  resources who master  English. To  overcome  the  problem, some short courses were conducted to improve the college subject teachers’  English  competence.  Service  English  Unit  (SEU), Diponegoro  University is  a  language  center  carrying  out  such  a training in cooperation with Univesitas Negeri Yogyakarta funded by  Program  Hibah  Kompetensi  Berbasis  Institusi  (PHKI)  DIKTI Jakarta. The training lasting for 27 hours covered the components as  follows:  lecture  preparation,  academic  language,  grammar  & phonetics, developing students’ learning and communication skills, course outline, project.Dalam  era  globalisasi  membuat  jaringan  yang  lebih  luas  antar universitas  urgen.  Untuk  mewujutkan kerjasama  semacam  itu beberapa  perguruan  tinggi  Indonesia  membuka  program internasional  tetapi  masalah  umum  yang  dihadapi  dalam  tingkat perguruan  tinggi  adalah  terbatasnya  sumberdaya  manusia  yang menguasai bahasa Inggris. Untuk mengatasi masalah ini, beberapa kursus  singkat  diselenggarakan  untuk  meningkatkan  kompetensi bahasa  Inggris  para  pengajar  matakuliah  bidang  studi.  Service English  Unit  (SEU),  Universitas  Diponegoro  merupakan  pusat bahasa  yang menyelenggarakan pelatihan semacam itu kerja sama dengan  Universitas  Negeri  Yogyakarta  (UNY)  yang  dibiayai  oleh Program  Hibah  Kompetensi  Berbasis  Institusi  (PHKI)  DIKTI Jakarta.  Pelatihan  yang  berlangsung  27  jam  meliputi  komponen sebagai  berikut: persiapan  kuliah,  bahasa  akademik,  grammar  & fonetik,  pengembangan  ketrampilan  belajar  dan  komunikasi peserta, silabus, proyek.